Empowering Women in Andhra Pradesh: Evaluating Government Policies and the Role of NGOs - Dr Sivasankar Mandal Baidya, Ch. Ravi Kiran, N. Sunil Kumar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
A vital component of growth that includes social, political, and economic aspects is the empowerment of women. In Andhra Pradesh (AP), India, this research looks at the influence of policies and the function of non-governmental organizations (NGOs) in empowering women. With a mixed-methods approach, the study integrates qualitative insights from focus groups and interviews with women recipients, government officials, and members of non-governmental organizations, with quantitative data from surveys. The results show that women's economic standing, social involvement, and safety have considerably increased as a result of government efforts such the "Stree Nidhi Credit Cooperative Federation Ltd." and the "Abhayam" mobile application. Organizations such as the Self-Employed Women's Association (SEWA) and Mahila Mandals have played a pivotal role in augmenting professional competencies, health consciousness, and legal literacy. Sociocultural hurdles still exist, though, and they prevent empowerment from being fully realized. The report emphasizes the value of coordinated efforts and suggests more cooperation between governmental and non-governmental organizations, broad awareness campaigns, capacity-building initiatives, and strong monitoring and assessment systems to guarantee long-term women's empowerment in AP.